HUBUNGAN FAKTOR RISIKO DENGAN JENIS SUB-TIPE MOLEKULAR KANKER PAYUDARA DI KOTA PADANG - Kurniawan, Arif Rasyidi; Harahap, Wirsma Arif; Kurniawati, Yulia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Risk factors that cause breast cancer have been a study related to racial, cultural, and socioeconomic factors. Therefore, breast cancer risk factors become important for prognosis and predictive in management. Currently, biomolecular breast cancer is divided into several subtypes, namely Luminal A, Luminal B, HER-2 overexpressive, and Triple-negative breast cancer. Objective: This study aims to determine the relationship between risk factors and the types of molecular subtypes of breast cancer in Padang City. Method: The type of research is analytical with a cross-sectional design. The research took place from April to August 2022 at RSUP Dr. M. Djamil Padang, RSI Ibnu Sina Padang, RSK Ropanasuri Padang and RSU Bunda BMC Padang. Results: The results showed that the most type of subtype was Luminal B (49.3%). Then, the type of TNBC (24.6%). Followed by HER-2 Overexpressive (11%). And the least is the type of Luminal A (10.1%). Most (89.9%) of patients were exposed to passive smoking. Most (87%) menopausal age is most at the age of under 50 years. Most (75.4%) have no family history of cancer. More than half (73.9%) did not use oral contraceptives for more than 12 months. More than half (72.5%) consumed fat and calories within normal limits. More than half (68.1%) were without sports activities. More than half (55.1%) of the age giving birth to their first child is found to be spanning the ages of 20 to 30 years. Almost half (47.8%) of breast cancer patients are obese. Based on the Chi-Square test and the Fisher test, showed that there was no association of risk factors with the type of molecular subtype. Conclusion: There is no relationship between risk factors and molecular subtypes of breast cancer in Padang City. Most types of molecular subtypes found Luminal B, followed by the type of TNBC, then HER-2 Overexpressive, and the least is Luminal A. The results of these findings are the same as other studies in Indonesia